Respuesta :
The summation indicates the sum from n = 1 to n = 3 of the expression 2(n+5).
2 (n+5) = 2n + 10
2n + 10 denotes an Arithmetic Series, with a common difference of two and first term as 12.
For n =1, it equals 12
For n = 2, it equals 14
For n = 3, it equals 16
So the sum from n=1 to n=3 will be 12 + 14 + 16 = 42
Sum of an Arithmetic Series can also be written as:
[tex] S_{n} = \frac{n}{2}(2a_{1} +(n-1)d)[/tex]
Using the value of a₁ and d, we can simplify the expression as:
[tex] S_{n} = \frac{n}{2} (24+2(n-1)) \\ \\ S_{n} =n (12+(n-1))\\ \\ S_{n} =n (11+n)[/tex]
This expression is equivalent to the given expression and will yield the same result.
For n=3, we get the sum as:
S₃ = 3(11+3) = 42
2 (n+5) = 2n + 10
2n + 10 denotes an Arithmetic Series, with a common difference of two and first term as 12.
For n =1, it equals 12
For n = 2, it equals 14
For n = 3, it equals 16
So the sum from n=1 to n=3 will be 12 + 14 + 16 = 42
Sum of an Arithmetic Series can also be written as:
[tex] S_{n} = \frac{n}{2}(2a_{1} +(n-1)d)[/tex]
Using the value of a₁ and d, we can simplify the expression as:
[tex] S_{n} = \frac{n}{2} (24+2(n-1)) \\ \\ S_{n} =n (12+(n-1))\\ \\ S_{n} =n (11+n)[/tex]
This expression is equivalent to the given expression and will yield the same result.
For n=3, we get the sum as:
S₃ = 3(11+3) = 42
Answer:
Sample Response: Substitute the values 1, 2, and 3 into the expression 2(n + 5), then find the sum. The summation is equal to 12 + 14 + 16 = 42. You can rewrite the summation as the sum of 2(n + 6) from 0 to 2.